Food chemical safety - Watson, D. H. 1952- (CRC Press ; Woodhead Pub., 2001)
Chemical contaminants in food, from pesticides and veterinary drug residues to contamination from food packaging, are a major concern for the food industry. Written by a distinguished international team of contributors, this authoritative collection describes the main chemical contaminants, their health implications, how they contaminate food products, methods of detection and how such contaminants can be controlled. Describes the main chemical contaminants of food, their health implications, how they contaminate food products, methods of detection and how such contaminants can be controlled.
Keywords: Food contamination.; Food additives.; Food adulteration and inspection -- Standards.; Food law and legislation.; elektronické knihy; electronic books